Multi-Intervention Scenarios in the Mangrove Blue Carbon Project Can Enhance Emission Reductions and Increase the Economic Value of Carbon - Aswin Rahadian; Lilik Budi Prasetyo; Yudi Setiawan; Cecep Kusmana (Department of Forestry, Faculty of Agriculture, University of Lampung, 2026)
Mangrove ecosystems provide globally important climate regulation services through long-term carbon sequestration, yet restoration programs frequently rely on single management interventions that may underestimate their mitigation potential. This study evaluated the climate mitigation performance of integrated blue carbon interventions across the northern coast of Java, Indonesia, by comparing conservation of intact wetlands with avoided deforestation, restoration of wetland ecosystems with active planting, and restoration with assisted natural regeneration. A spatially explicit Tier 3 carbon accounting framework was developed by integrating multi-temporal Landsat observations (1972-2025), Random Forest land-cover classification, mangrove carbon-stock data, field-derived growth measurements, and scenario-based greenhouse gas accounting over a 30-year project horizon. The results indicate an average potential emission reduction of 8.67 Mt CO2e/year across the study area. Among the evaluated interventions, coastal erosion control through restoration with assisted natural regeneration achieved the highest mitigation performance (120 tCO2e/ha/year), nearly four times that of planting-based rehabilitation (32 tCO2e/ha/year). Over a 30-year simulation period, these scenarios are projected to generate 210 Mt CO2e of tradable carbon units, equivalent to an average of 7 Mt CO2e/year. At a carbon price of USD 5/t CO2e, this volume could have an economic value exceeding USD 35 million per year. These findings demonstrate that integrated mangrove protection and restoration strategies can deliver substantial climate mitigation outcomes while creating significant economic incentives through carbon finance mechanisms. Keywords: blue carbon, carbon credit, carbon project, mangrove ecosystem, multi-Intervention scenarios